PETROLOGY AND MINERALOGY OF VOLCANIC ROCKS FROM TELAGA RANO VOLCANIC COMPLEX, WEST HALMAHERA, NORTH MALUKU PROVINCE - NOERMA ARIFA 12013080 , ADZKIA
Telaga Rano volcanic complex consists of six volcanoes namely Mount Talaga Rano, Mount Sahu, Mount Onu, Mount Popolodio, Mount Alon, and Mount Sailulu that are located in West Halmahera, North Maluku Province. Petrology, mineralogy, characteristic of magma (composition, affinity, temperature, pressure), and magma evolution of Mount Telaga Rano, Mount Sahu, and Mount Onu were studied in this research. Petrology and mineralogy analysis were conducted on sixteen volcanic rock samples of Mount Talaga Rano, Mount Sahu, and Mount Onu. Mineral chemistry data were analyzed from eleven representative samples from lava of Mount Talaga Rano, Mount Sahu, and Mount Onu using SEM-EDS JEOL JSM-IT-300. Mount Telaga Rano has andesitic magma with pressure of 5 kbar and temperature is about 920?-1170?C. The andesite lava of Mount Telaga Rano is pyroxene andesite. Processes of magma evolution of Mount Telaga Rano is influenced by adiabatic decompression when magma moves up toward the shallower magma chamber and recharge of more primitive and Ca-rich magma. Mount Sahu has andesitic magma with pressure of 2,2-5,4 kbar and temperature is about 946?-1007?C. The andesite lava of Mount Sahu is pyroxene andesite. Convection, adiabatic decompression, and recharge of Ca-rich magma in the magma plumbing system affect the evolution of the andesitic magma. Intensity of Ca-rich magma injection is more intesive and change the magma composition into basaltic. Basaltic magma of Mount Sahu has pressure of ?5 kbar and temperature is about 1192?- 1330?C. The basaltic lava of Mount Sahu is olivine basalt. Beside recharge process, adiabatic decompression and convection in the shallower magma chamber also effect the evolution of Mount Sahu basaltik magma. Mount Onu has andesitic magma with pressure of 5 kbar and temperature is about 970?-1090?C. The andesite lava of Mount Onu is pyroxene andesite. The process in the magma plumbing system of Mount Onu that affects the evolution of magma are adiabatic decompression and convection process in the shallower magma chamber, so the magma chamber become more dinamic. The process of recharge Ca-rich magma also occur but not intensive.